Nitric oxide implication in the control of seed dormancy and germination - Arc, Erwann; Galland, Marc; Godin, Béatrice; Cueff, Gwendal; RAJJOU, Loïc (Frontiers in Plant Science, 2013)
Germination ability is regulated by a combination of environmental and endogenous signals with both synergistic and antagonistic effects. Nitric oxide (NO) is a potent dormancy-releasing agent in many species, including Arabidopsis, and has been suggested to behave as an endogenous regulator of this physiological blockage. Distinct reports have also highlighted a positive impact of NO on seed germination under sub-optimal conditions. However, its molecular mode of action in the context of seed biology remains poorly documented. This review aims to focus on the implications of this radical in the control of seed dormancy and germination. The consequences of NO chemistry on the investigations on both its signaling and its targets in seeds are discussed. NO-dependant protein post-translational modifications are proposed as a key mechanism underlying NO signalling during early seed germination.